Impact of depreciation accounting on financial health in telecommunication industry with reference to accounting standards and IFRS (International Journal of Food and Nutritional Sciences, 2022)
This article examines the effects of depreciation accounting on the financial well-being of telecom firms, focusing on accounting standards and International Financial Reporting Standards (IFRS). There are major ramifications for financial reporting, performance assessment, and investment decision-making due to depreciation accounting's importance in representing the actual economic worth of assets. The choice of assumptions and procedures for depreciation may have a significant impact on financial statements and important financial indicators in the fast-paced and capital-intensive telecommunications industry, where new technologies quickly make assets outdated. The purpose of this research is to examine the telecom industry's depreciation accounting methods in light of various accounting rules and IFRS. It takes a look at how profitability, liquidity, solvency, and asset turnover are affected by different assumptions about residual value, useful life estimates, and depreciation procedures. Also discussed is how the openness and comparability of financial data among telecoms firms throughout the world are impacted by the degree to which certain accounting rules are followed or IFRS is adopted. Methods include a survey of the current literature, an examination of financial data from telecom companies, and a comparison of depreciation policies and the indices of financial health that they affect. The study's findings may help telecommunications businesses, regulators, investors, and others better grasp the intricacies of depreciation accounting and how they affect financial stability and performance. The results also add to the continuing discussion about accounting standard convergence and the need to standardise financial reporting across sectors and countries